Engineering Verification of Key Technologies for Rail Transit Stray Current Protection - JIN Shoujie; MA Jiansheng; OUYANG Kai; LIU Yubei; ZHAO Yunyun; LIN Xiaohong (Chengshi guidao jiaotong yanjiu)
[Objective] In order to solve the problem of stray current corrosion on metro lines, it is necessary to conduct engineering verification of the key technologies for stray current protection in urban rail transit. [Method] The high-insulation concrete is introduced. A new type of fully insulated rail fastener is designed, and static and dynamic test methods are used to verify the insulation performance of the track steel rail against the ground. The static test includes measuring the rail-to-ground resistance parameters, and the dynamic test simulates the metro operating conditions to detect the changes of rail-to-ground transition resistance during the actual metro operation. [Result & Conclusion] By setting a fully enclosed eaves structure rail pad and extending insulated gauge blocks, and other methods, the new type of fully insulated rail fastener can increase the creepage distance and improve the surface resistance of the rail fastener. Both the high-insulation concrete and the fully insulated rail fastener can effectively improve the rail-to-ground transition resistance. Compared with the traditional track installation schemes, the overall insulated fastener plus silicon-based nano-insulation wrapping scheme exhibits the most significant effect on improving the rail-to-ground transition resistance. The new type of insulating materials and the fastener system can maintain good insulation performance under different working conditions, and effectively reduce the leakage of track stray current.